Fiscal policy, the current account, and the twin deficits hypothesis. - Bongers-Chicano, Aneli María; Torres-Chacón, José Luis (My University, 2019)
Relationship between Öscal policy and the current account. Traditional view suggests that a Öscal expansion should lead to a worsening in the current account, contrary to the Ricardian view, in which there is no systematic relationship between budget and current account deficits.
Keywords: Política fiscal; Twin deficits; Fiscal Policy